A colourimetric evaluation of the effect of bacterial contamination on teeth stained with blood in vitro: Evaluation of the efficacy of two different bleaching regimes. (16th April 2018) - Wang, S; Cathro, P; Heithersay, G; Briggs, N; Ratnayake, J; Zilm, P
Abstract: Background: Tooth discolouration could occur due to bacterial contamination in traumatized teeth. Hydrogen peroxide is the commonly used bleaching agent. However, due to concerns over safety, alternative bleaching regimes such as sodium perborate (S) and thiourea‐hydrogen peroxide (T) have been investigated. Methods: Apices resected and pulp extirpated 99 premolars were divided into two groups. Group 1 and 2 was injected with blood and blood/bacteria, stored anaerobically for 35 days. The two groups were treated by bleaching with water, S or T. Teeth were rebleached after 7 days. Colourimetric evaluation was assessed using digital imaging, CasMatch standardization and CIE L * a * b colour system preoperatively, 35 days of staining and 7 and 14 of bleaching. A linear mixed model with fixed effects of time, group and bleach was used to examine colour difference. Results: Blood‐stained teeth were significantly redder and darker on day 35 compared with blood/bacteria‐stained teeth. After bleaching, blood‐stained teeth retained significant redness compared with blood/bacteria‐stained teeth using either S or T. T produced a significantly whiter shade in both the groups after 14 days. Conclusions: Blood‐stained teeth were significantly darker and red compared with blood/bacteria‐stained teeth. T bleaching regime was more effective than S.